ANALISIS MODEL PENGINTEGRASIAN TEKNOLOGI DALAM PEMBELAJARAN MENGGUNAKAN SAMR DAN TPACK: TEORI DAN PRAKTIK DALAM PENGEMBANGAN MEDIA PEMBELAJARAN PAI - Aziroh, Khisma Maula Umadatul; Salsabila, Alifia Zulfi; Sutiah, Sutiah (Universitas Tribhuwana Tunggadewi, 2025)
This study aims to describe models of technology integration, namely SAMR and TPACK. Each model explains the components contained therein, which certainly have advantages and disadvantages in their application in PAI learning. The SAMR framework is used to evaluate the level of technology integration in learning, while TPACK helps identify the knowledge required for teachers to effectively combine technology with pedagogy and content. The method used in this study is library research, which involves using relevant literature as a source of information. The findings of this study indicate that: (1) the use of the SAMR model can improve students' critical thinking skills and learning motivation, as well as make the learning process more modern and effective. (2) Although there is significant potential to increase students' interest and teachers' positive perceptions of technology use, challenges such as teachers' readiness and competence, as well as the integration of technology into the curriculum, need to be addressed. (3) Teachers require ongoing training and support to optimise the use of technology in learning, enabling them to effectively apply the SAMR and TPACK models.